A Survey of Information Sources Used by Psychiatrists - Bowden, Charles L. (1971)
To study the information sources of psychiatrists, we sent a questionnaire to 400 randomly selected members of the American Psychiatric Association. Seventy-four percent responded. Journals and books (in that order) were the most important information sources. The average number of journals regularly read was 4.3. An average of 9.1 books had been read during the preceding twelve months. Twenty-eight percent of books were obtained through a library. Sixty-nine percent of the respondents use a medical library at least monthly. Important differences were found by type of practice. For example, academicians reported reading almost 19 books the preceding year; private practitioners, 6.4. We conclude that a major aim in the postgraduate education of psychiatrists should be instruction in the use of all information services. In addition, abstracts and an authoritative annual review should help psychiatrists keep up in areas outside their special interest.